How pharmacy's adoption of social media can enhance patient outcomes - Bell M; Douglas J; Cutts C (Dove Medical Press, 2014)
Maria Bell, Jan Douglas, Christopher CuttsCentre for Pharmacy Postgraduate Education, Manchester Pharmacy School, University of Manchester, Manchester, UKAbstract: Social media is progressively being used for sharing health information and for networking among health professionals and patients; this is particularly evident among the younger age groups. There is great potential for pharmacy to engage in the utilization of such platforms to improve health outcomes, and this paper explores some of the areas where social media is already in use in pharmacy and potential areas where using social media could make a positive impact on the determinants of health. The literature around this subject is limited; nevertheless, the number of published studies has increased in recent years. This paper concentrates on the use and application of social media by pharmacy to improve health outcomes. The subject was explored in five main areas: provision of medicines information, safer use of medicines, medicines use in chronic disease, implementation of evidence-based medicine and guidelines, and finally clinical research. In each of these areas, there is an increase in uptake and use of social media platforms by pharmacists and other health care professionals to improve patient outcomes. A variety of the more popular social media platforms have been used by health care professionals and the relative merits of these are discussed within each of the subject areas and consideration given to their application in pharmacy practice. It is evident that the majority of social media users fall into the younger age bracket, which is understandable. However, the majority of patients living with long-term conditions typically fall into the older age bracket (over 65 years of age) and this should be taken into account when utilizing social media platforms to improve health outcomes.Keywords: social media, pharmacy, outcomes, impact, health